![\qquad\qquad\huge\underline{{\sf Answer}}♨](https://tex.z-dn.net/?f=%5Cqquad%5Cqquad%5Chuge%5Cunderline%7B%7B%5Csf%20Answer%7D%7D%E2%99%A8)
Since it's a Trapezoid with its non - parallel sides equal to one another,
![\qquad \sf \dashrightarrow \:\angle A + \angle P = 180](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%5Cangle%20A%20%2B%20%5Cangle%20P%20%3D%20180)
[ By forming co - interior angle pair ]
![\qquad \sf \dashrightarrow \:\angle A +100 = 180](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%5Cangle%20A%20%2B100%20%3D%20180)
![\qquad \sf \dashrightarrow \:\angle A = 180 - 100](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%5Cangle%20A%20%3D%20180%20-%20100)
![\qquad \sf \dashrightarrow \:\angle A = 80](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%5Cangle%20A%20%3D%2080%20)
Now, similarly,
![\qquad \sf \dashrightarrow \:\angle A + \angle R = 180](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%5Cangle%20A%20%2B%20%5Cangle%20R%20%3D%20180)
![\qquad \sf \dashrightarrow \: \angle R + 80 = 180](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%20%5Cangle%20R%20%2B%2080%20%3D%20180)
![\qquad \sf \dashrightarrow \: \angle R = 100](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%20%5Cangle%20R%20%20%3D%20100)
Similarly,
![\qquad \sf \dashrightarrow \angle K + \angle R = 180](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5Cangle%20K%20%2B%20%5Cangle%20R%20%3D%20180)
![\qquad \sf \dashrightarrow \angle K + 100 = 180](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5Cangle%20K%20%2B%20100%20%3D%20180)
![\qquad \sf \dashrightarrow \angle K = 80](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5Cangle%20K%20%20%3D%2080)
Answer:
wheres your graph?
Step-by-step explanation:
i could do this with a graph lol
Answer:
Step-by-step explanation:
1 False
2 True
3 False
4 false
lol that was ezy
x+y=5
-x -x
Equals:
y=-x+5
Now you have:
y=-x+5
x-y=1
Insert -x+5 into y
x-x+5=1
Combine like terms
2x+5=1
Subtract 5.
2x=-4
Divide 2.
Answer: x=-2